2004
DOI: 10.1152/ajpgi.00228.2004
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative DNA damage and DNA repair enzyme expression are inversely related in murine models of fatty liver disease

Abstract: Mitochondrial generation of reactive oxygen species (ROS) is increased in mice with fatty livers induced by genetic obesity, chronic consumption of ethanol, or methionine/choline-deficient diets. Both nuclear and mitochondrial (mt) DNA are targets for ROS-induced damage and accumulate hydroxylated bases, such as 8-hydroxy-2'-deoxyguanosine (8-oxoG) and base substitution of adenine with 8-oxoG (A*8-oxoG), that introduce mutations that promote cancer as well as cell death. The mammalian homolog of the bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(85 citation statements)
references
References 45 publications
1
83
1
Order By: Relevance
“…Caspase-3 activation and hepatocyte apoptosis have been shown to be prominent features of different experimental models of NAFLD-as well as human NAFLD-and to correlate with disease severity. 5,13 To determine whether caspase-3-generated CK-18 fragments are also increased in the livers of NAFLD patients, immunohistochemistry using the M30 monoclonal antibody was performed (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Caspase-3 activation and hepatocyte apoptosis have been shown to be prominent features of different experimental models of NAFLD-as well as human NAFLD-and to correlate with disease severity. 5,13 To determine whether caspase-3-generated CK-18 fragments are also increased in the livers of NAFLD patients, immunohistochemistry using the M30 monoclonal antibody was performed (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, because NEIL1 can initiate repair in single-stranded and bubble structures, the lack of this repair may lead to severe decreases in mitochondrial replication and transcription rates and, thus, an overall disruption of energy homeostasis. The hypothesis that impaired DNA repair capacity of oxidative damage could increase susceptibility to fatty liver disease has previously been proposed by the Diehl group (33). They demonstrated that the greatest accumulation of 8-oxoguanine lesions and the greatest amount of hepatocyte cell death occurred in their models in which the levels of MYH, the glycosylase responsible for initiating the removal of adenine in the A⅐8-oxoguanine mispair, was the least.…”
Section: Discussionmentioning
confidence: 97%
“…This would have the effect to compromise the functioning of the oxidative phosphorylation system as a result of the loss of mitochondrial gene products that make up segments of the respiratory chain; subsequently leading to more ROS production. This concept is supported by observations of significant mtDNA mutations and abnormalities in NASH patients [67,68] and in an animal model of fatty liver disease [60]. Whether these mtDNA defects translate into decreased activity and content of the respiratory complexes in obesity induced fatty liver disease is not known.…”
Section: Mitochondria Dysfunction In Fatty Liver Diseases -Bioenergetmentioning
confidence: 92%
“…More importantly, the molecular mechanisms responsible for oxidant production in obesity induced fatty liver are not known, especially because mitochondrial un-coupling has been shown in experimental models of NAFLD [51]. Studies using liver mitochondria from ob/ob mice have however demonstrated increased O 2 • − compared to mitochondria from lean mice [60,61]. Possible mechanisms for enhanced mitochondrial ROS production include molecular defects within Complexes I and III, as well as increases in RLS, and TNFα mediated ceramide [22,59,62,63].…”
Section: Mitochondria Dysfunction In Fatty Liver Diseases -Bioenergetmentioning
confidence: 99%